Absence of close linkage between benign hereditary chorea and the locus D4S10 (probe G8). - Quarrell, O W (1988)
A genetic linkage study between benign hereditary chorea and the locus D4S10 using the DNA probe G8 has shown two recombinations in five small families. There were negative lod scores at recombination fractions that show conclusive evidence of linkage in 16 larger British Huntington's disease families. We suggest that although benign hereditary chorea and Huntington's disease may have some clinical similarities they are probably at two different loci.